The immediate impact of a brief rural mental health workforce recruitment strategy. Issue 2 (3rd May 2016) - Sutton, Keith; Patrick, Kent; Maybery, Darryl; Eaton, Kaytlyn
Abstract : This study examines the immediate impact of a 5-day intervention designed to attract urban trained allied health and nursing students to rural mental health work. The sequential quantitative-qualitative confirmatory mixed methods study employed pre- post programme online surveys and individual semi-structured interviews. Paired sample t -tests showed significant post-programme change in participants' attitudes to working in a rural setting but less pronounced changes in attitude towards rural life. Content analysis of the interviews validated and augmented these results. Students frequently remarked about the range of employment and career opportunities available in rural areas; however, far fewer interview responses related to the non-work aspects of rural life. The study demonstrates that a brief rural workforce recruitment intervention has a differential impact upon participants' attitudes to living and working in a rural area. The findings have implications for attracting new mental health professionals to rural practice.